Green manure incorporation enhanced soil labile phosphorus and fruit tree growth - Yang, Yuanyu; Zhang, Jianwei; Chang, Xia; Chen, Lunlun; Liu, Yongmin; Xu, Qingwei; Wang, Mengjuan; Yu, Haiyan; Huang, Renmei; Zhang, Jie; Hu, Yingxiao; Hu, Qijuan; et al. (Frontiers in Plant Science, 2024)
The incorporation of green manures substantially enhances the conversion of external phosphorus (P) fertilizers and soil-reserved P into forms readily available to plants. The study aims to evaluate the influence of green manure additions on soil phosphorus dynamics and citrus growth, considering different green manure species and initial soil phosphorus levels. Additionally, the research seeks to elucidate the microbiological mechanisms underlying the observed effects.Methods: A citrus pot experiment was conducted under both P-surplus (1.50 g•P•kg -1 ) and P-deficient (0.17 g•P•kg -1 ) soils with incorporating legume (Leg), non-legume (Non-Leg) or no green manure residues (CK), and 18 O-P labeled KH2PO4 (0.5 g, containing 80‰ δ 18 Op) was additionally introduced to trace the turnover characteristics of chemical P fertilizer mediated by soil microorganisms.In P-surplus soil, compared with the CK treatment, the Leg treatment significantly increased soil H2O-Pi (13.6%), NaHCO3-Po (8.9%), NaOH-Pi (9.5%) and NaOH-Po (30.0%) content. It also promoted rapid turnover of P sources into H2O-Pi and NaHCO3-Pi pools by enhancing the phoC (576.6%) gene abundance. In contrast, the Non-Leg treatment significantly augmented soil H2O-Pi (9.2%) and NaHCO3-Po (8.5%) content, facilitating the turnover of P sources into NaHCO3-Pi pools. Under P-deficient soil conditions, compared with the CK treatment, the Leg treatment notably raised soil H2O-Pi (150.0%), NaHCO3-Pi (66.3%), NaHCO3-Po (34.8%) and NaOH-Pi (59.0%) content, contributing to the transfer of P sources into NaHCO3-Pi and NaOH-Pi pools. This effect was achieved through elevated ALP (33.8%) and ACP (12.9%) activities and increased pqqC (48.1%), phoC (42.9%), phoD (21.7%), and bpp (27.4%) gene abundances. The Non-Leg treatment, on the other hand, led to significant increases in soil NaHCO3-Pi (299.0%) and NaHCO3-Po (132.6%) content, thereby facilitating the turnover of P sources into NaHCO3-Pi and NaOH-Pi pools, except for the phoC gene abundance. Both Leg and Non-Leg treatments significantly improved citrus growth (7.3-20.0%) and P uptake (15.4-42.1%) in P-deficient soil but yielded no substantial effects in P-surplus soil. In summary, introducing green manure crops, particularly legume green manure, emerges as a valuable approach to enhance soil P availability and foster fruit tree growth in orchard production.